2020
DOI: 10.1080/23311843.2020.1807275
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for improved solid waste management services and associated factors among urban households: One and one half bounded contingent valuation study in Bahir Dar city, Ethiopia

Abstract: To cite this article: Kassahun Tassie & Birara Endalew | (2020) Willingness to pay for improved solid waste management services and associated factors among urban households: One and one half bounded contingent valuation study in Bahir Dar city, Ethiopia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
(63 reference statements)
5
10
1
2
Order By: Relevance
“…Respondents who generated 2 sacks of 50 kg of solid waste per week were more likely to pay for improving solid waste management compared to those who produced 1 sack of 50 kg of solid waste weekly. This finding is in line with previous studies that found individuals who generated huge amounts of solid waste were more likely to pay for improving solid waste management services [2,24,25]. In addition, we found that respondents who had access to solid waste management services were almost four times more likely to pay than those who had no access.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Respondents who generated 2 sacks of 50 kg of solid waste per week were more likely to pay for improving solid waste management compared to those who produced 1 sack of 50 kg of solid waste weekly. This finding is in line with previous studies that found individuals who generated huge amounts of solid waste were more likely to pay for improving solid waste management services [2,24,25]. In addition, we found that respondents who had access to solid waste management services were almost four times more likely to pay than those who had no access.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that 86.3% of the study participants were willing to pay for improving solid waste management services. This is comparable with that of the study conducted in Macau, 85.4% [30]; Gondar, Ethiopia, 87.3% [32]; Bahir Dar, Ethiopia, 86.3% [24]; Injibara town, Ethiopia, 81.06% [25]; and Jimma town, Ethiopia, 83.5% [2]. However, this finding is higher than the study finding in Nepal, 61% [18]; Uganda, 48.1% [22]; and Tanzania, 63% [28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Tana, the headwaters of the Blue Nile, and is a significant vacationer city in Ethiopia (Fenta, 2017). It has a level earth structure which is located at 11.5742 °N, 37.3614 °E, and expanded quickly throughout the 20th century; today, sewage release into Lake Tana and the Blue Nile has turned into a genuine and profoundly noticeable problem (Tassie and Endalew, 2020). The name Bahir Dar is associated with its nearness to the two water assemblages of Lake Tana and River Abay (Blue Nile).…”
Section: Description Of the Study Area And Site Selectionmentioning
confidence: 99%
“…Tujuan penelitian ini adalah untuk mengukur dan menganalisis kesediaan membayar Badan Usaha Milik Swasta (BUMS) apabila ikut serta dalam melakukan pengembangan kawasan naturalisasi sungai, maka Pemerintah Provinsi DKI Jakarta memberikan insentif yaitu berupa penambahan nilai KLB. Beberapa penelitian terkini sebelumnya telah mengukur kesediaan untuk membayar, baik oleh konsumen maupun perusahaan, atas jasa lingkungan (Kono et al, 2020;Liu, 2020;Mondal & Patel, 2018;Nielsen-Pincus et al, 2017;Opačak & Wang, 2019;Tassie & Endalew, 2020;Xu et al, 2020;Zhang et al, 2021). Penelitian-penelitian tersebut telah mengukur kesediaan membayar konsumen maupun perusahaan untuk jasa lingkungan yang berbeda-beda dengan latar belakang berbagai negara yang berbeda.…”
Section: Pendahuluanunclassified